O12 Mission and strategic objectives for the RCSI'S new academic & educational building. (5th November 2017) - Murray, JM; Sullivan, C
Abstract : Introduction/Rationale: The opening of RCSI's new state of the art Academic and Educational Building will offer exciting opportunities for the delivery of simulation based healthcare education (SBE). With an expected footfall of over 4000 students per year, a clear vision and strategy needs to be defined. We used the 'Balanced Score Card' concept 1 (BSC) as a tool for implementation and measurement of this strategy. The BSC is an example of a closed-loop controller and monitors the performance of all or part of an organisation, towards its strategic or operational goals. To be useful, it should include the right measures and targets. Methods: We used the "4 perspective" approach of the BSC to identify what measures to use to track the implementation of our strategy. These were: Financial: "How do our stakeholders see us?", Customer: encourages the identification of measures that answer the question "How do our students see us?", Internal business processes: encourages the identification of measures that answer the question "What must we excel at?", Learning and growth: encourages the identification of measures that answer the question "How can we continue to improve, create value and innovate?" Results/Findings: The BSC allowed us to develop Key Performance Indicators (KPIs) and develop our strategic goals. From a Financial perspective, KPIs included position in the University rankings, Centre usage and costing, and external business collaborations. From an Internal Processes perspective, they included the quantification and analysis of learning and the implementation of lean management principles. From a Learning and Growth Perspective. KPIs included strong personal development plans, educational scholarship and team leadership. Finally, from our students' perspective, they comprised internationalisation, innovation and modern learning. Conclusion: The use of the BSC with defined KPIs allowed the development of a clear strategic focus to our organisation. Reference: 1. Kaplan Robert S, Norton DP. The balanced scorecard – Measures that drive performance. Harvard Business Review (January–February) 1992:71–79.